Effect of Fineness of Limestone Powder on Compressive and Splitting Tensile Strengths and Modulus of Elasticity of Concrete mixed with Fly Ash and Limestone Powder - เพาะบุญ สุรสิทธิ์; กร้ำมาตร ปิติศานต์ (Frontiers in Engineering Innovation Research, 2013)
This paper presents the study results of the effect of fineness of limestone powder on the mechanical properties of concrete mixed with fly ash and limestone powder. Limestone powder with haring fineness by representing as a mean particle size (d ) equal to 2, 8 and 15 micrometers (um) was aken into account by replacing in Type 1 Portland cement of the replacement percentage of 0%,5%,10% and 20% by weight and blended with fly ash at replacement percentage of 30%, 25%, 20% and 10% by weight. The basic properties of all materials which are chemical composition,physical including specific gravity and Blaine fineness were investigated. Mechanical properties which are the compressive and splitting tensile strengths and modulus of elasticity were tested. Results show that the compressive strengths of early-age concrete containing limestone powder have higher tendency than those of conventional concretes. In addition, the limestone powder-fly ash concretes have also high compressive strength than those of conventional concretes. Furthermore, the splitting tensile modulus of elasticity of concrete containing fly ash and limestone powder have a similar heirs compressive strength. In summary, the fineness of limestone powder has higher mechanical properties, which has higher fineness limestone powder has higher mechanical proper lower one.